Automatic alignment technique for the suspended coil in the joule balance. (28th October 2021) - Bai, Yang; Wang, Dawei; Li, Zhengkun; Lu, Yunfeng; Hu, Pengcheng; He, Qing; Zhang, Zhonghua; Tan, Jiubin
Abstract: An automatic alignment technique was developed for the joule balance to reduce the uncertainty caused by alignment errors. Using the flexures and decoupling structure of the suspended coil, the proposed alignment system can automatically recognize the linear relationship between the initial position and posture of the suspended coil when the current is off, and its parasitic horizontal linear and angular displacements when the current is on. Subsequently, several actuators including mini-motors and an X – Y stage are controlled to adjust the position and posture of the coil, minimizing the parasitic forces and torques and reducing them by approximately 100 times in comparison with the alignment results of the joule balance obtained in 2019, whilst maintaining the adjustment time to several minutes only.